Renal Function in Cirrhosis: A Critical Review of Available Tools - Piano, Salvatore; Brocca, Alessandra; Angeli, Paolo (Seminars in Liver Disease, 2018)
Patients with cirrhosis have a high prevalence of renal dysfunction. The susceptibility to renal dysfunction is due to both the severe splanchnic arterial vasodilation and the systemic inflammation observed in these patients. An accurate assessment of renal function is recommended in all patients with cirrhosis. Indeed, the renal function assessment guides the management of patients, helps to refine prognosis and to define transplant strategies. Despite its limitations, serum creatinine is still the most used biomarker for the estimation of glomerular filtration rate (GFR) and the assessment of acute kidney injury (AKI) in patients with cirrhosis. New biomarkers of GFR such as cystatin C may improve the assessment of GFR and the prognostic stratification in these patients. AKI is a life-threatening complication and needs a timely management. The differential diagnosis between hepatorenal syndrome (HRS) and acute tubular necrosis (ATN) is tricky in clinical practice. New biomarkers of kidney injury, such as neutrophil gelatinase-associated lipocalin and interleukin-18, represent useful tools in refining the discrimination between HRS and ATN. Patients with HRS need a prompt treatment with vasoconstrictors and albumin and a rapid evaluation for liver transplant eligibility. In this article, the authors reviewed the available tools in the diagnosis and management of renal dysfunction in cirrhosis.
Keywords: hepatorenal syndrome; liver transplantation; terlipressin; renal failure; albumin